Characterization of the structure and molecular composition of scales in Teleost Fish - Estêvão, Dulce (2005)
Fish scales are an important source of calcium which may be mobilized in response to endocrine factors. To better understand this process it is necessary to understand the structure of this tissue. General histological staining methods and in situ hybridization were utilized to establish the structural organization of sea bream and tilapia scales. The general architecture of the scale has been characterized and putative osteoblasts and osteoclasts identified in both species.